Arrangement of Burn Status for Emergency Management, Monitoring, and Evaluation of Burns in Saiful Anwar General Hospital in Malang, East Java, Indonesia - Wihastyoko, Herman Yosef Limpat; Agustina, Wilma; Gersom, Camoya (Future Science, 2018)
The article proposes an arrangement of burn status for the management of severe based on a review of management of burns. More than 95% of burns are associated with fatal fires and occur in low to middle income countries. A coordination between health officers within health facilities is crucial to provide proper management for severe burns. There is no standard yet for burn status in Indonesia. Burn status may provide better management of patients who are admitted with burns. In this article, the set of burn status was arranged for the management of patients with burns in the Saiful Anwar General Hospital. There are 3 types of burn status in this paper each for the respective use of emergency management, burn unit monitoring, and wound care evaluation. The purpose of this burn status is to facilitate a better coordination between health officers regarding management of burns in Saiful Anwar General Hospital. This paper can also become the basis of further studies regarding burns as a tool to collect data or as a basis to pioneer the standard of burn status in Indonesia to further improve the general quality of burn care and research in Indonesia. The system of medical record for patients is generally carried out to keep a record of the patient's disease progression, including the diagnosis and treatment plans carried out by doctors and medical personnel which are involved.